Methamphetamine use is associated with high levels of depressive symptoms in adolescents and young adults in Rural Chiang Mai Province, Thailand - Lauren E. Dimiceli (2018)
© 2016 DiMiceli et al. Background: High levels of depressive symptoms often occur among individuals that use or that are dependent on methamphetamine (MA). Thailand is currently experiencing an epidemic of MA use among youth. Understanding the nature of the relationship between depressive symptoms and MA use and identifying those most at risk can further understanding of prevention and treatment options for youth who use MA and present with depressive symptoms. Methods: In 2011, we conducted a cross sectional epidemiologic study that examined associations between MA use and high levels of depressive symptoms among adolescents and young adults aged 14-29 living in Chiang Mai province, Thailand. A combination of cluster and systematic sampling was conducted to obtain a study sample of participants actively recruited in Chiang Mai province. Depressive symptoms were measured using a Thai translation of the Centers for Epidemiologic Studies Depression scale (CES-D). The independent variables measured reported lifetime and recent MA use within the past 3 months. Multivariate logistic regression models were used to assess associations between MA use and high levels of depressive symptoms. Results: Approximately 19 % (n = 394) of the sample reported ever having consumed MA and 31 % (n = 124) of lifetime users reported recent MA use within the past 3 months. Recent MA use was associated with high levels of depressive symptoms (aPOR recent use: 2.60, 95 % CI: 1.20, 5.63). Conclusions: This is one of the first studies to examine the association between MA use and high levels of depressive symptoms in a general Thai population. The odds of having high levels of depressive symptoms was significantly greater among recent MA users compared to non-users. These findings support the need for policies, programs and interventions to prevent and treat depressive symptoms presenting among MA using Thai adolescents and young adults in rural Chiang Mai province, Thailand to aid in cessation of MA use. Furthermore, additional research is needed to investigate treatment options for adolescents and young adults in Thailand that use MA and present with high levels of depressive symptoms.